Jugando con mi cuerpo - Fernandez Castillo, Liliana (2018)
In the theoretical framework of our session, it is emphasized, the recognition of each boy and girl with which they know and value themselves as they are and this helps them to a healthy social coexistence. Each student recognizes their universal needs such as food, health, rest, etc. and characteristics and own interests; recognizing themselves as active members of their family and of the various social groups to which they belong, with duties and rights for all boys and girls. Establishes interpersonal relationships by developing social skills that allow them to accept others, respecting their cultural differences and valuing collaborative work, in a caring and committed way, in different settings. Girls and boys build their identity based on the recognition and assessment of their personal characteristics and the discovery of its possibilities.